2015
DOI: 10.1016/j.neuron.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Interactions between Proprioceptive and Cutaneous Signals in Primary Somatosensory Cortex

Abstract: The classical view of somatosensory processing holds that proprioceptive and cutaneous inputs are conveyed to cortex through segregated channels, initially synapsing in modality-specific areas 3a (proprioception) and 3b (cutaneous) of primary somatosensory cortex (SI). These areas relay their signals to areas 1 and 2 where multimodal convergence first emerges. However, proprioceptive and cutaneous maps have traditionally been characterized using unreliable stimulation tools. Here, we employed a mechanical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
96
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 63 publications
13
96
1
Order By: Relevance
“…However, mounting evidence suggests that signals from distinct somatosensory submodalities are in fact combined in the CNS, and that most tactile percepts rely on multiple submodalities (Saal and Bensmaia, 2014). For example, a recent study found that all areas of somatosensory cortex receive input from both touch and proprioceptive neurons (Kim et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, mounting evidence suggests that signals from distinct somatosensory submodalities are in fact combined in the CNS, and that most tactile percepts rely on multiple submodalities (Saal and Bensmaia, 2014). For example, a recent study found that all areas of somatosensory cortex receive input from both touch and proprioceptive neurons (Kim et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, this analysis revealed significant activation in the frontal eye field contralateral to the pathological direction, and, in the opposite hemisphere, the ipsilateral postcentral sulcus, and supramarginal gyrus (Figure 4). Although proprioceptive information is processed in all subfields of primary somatosensory cortex, Brodmann’s area 3a (in the depth of the central sulcus) seems to be most important, followed by Brodmann’s area 1 and 2 (the latter located in the postcentral sulcus) (49). The middle cingulate gyrus is activated primarily in relation to movement execution, while the regions surrounding the frontal eye fields are premotor areas involved in motor planning (46).…”
Section: Discussionmentioning
confidence: 99%
“…Examinations of widespread and multidigit interactions in area 3b have added to our understanding of early stages of somatosensory processing to incorporate neurons with larger response fields that show reductions as well as increases in firing rate when discrete regions of skin are touched (DiCarlo et al 1998;Fitzgerald et al 2006b;Friedman et al 2008;Kim et al 2015;Reed et al 2008Reed et al , 2011Thakur et al 2006Thakur et al , 2012. Still, little information is available about the inhibitory components of the receptive field (RF) of neurons related to the hand and arm in primary somatosensory cortex in primates.…”
mentioning
confidence: 99%